Guidelines for use of fluorides in Australia: update 2019. (26th January 2020) - Do, LG; ,
Abstract: Fluoride use is the cornerstone of dental caries prevention. There are numerous sources of fluoride which might have different balance of risks and benefits. The first National Guidelines for Use of Fluorides in Australia were developed at a national Workshop in 2005, and updated in 2012. Since then, more evidence on the balance of risks and benefits of fluoride has become available. A third national Workshop was convened in 2019 to update the Guidelines for Use of Fluorides in Australia.